A vida danificada em Theodor Adorno : dos afetos da economia política à economia política dos afetos - Souza, Talins Pires de (2017)
The next words investigate the social economy that is recognized when a rationality is determined and also they tell about devices that turn the human relationship eminently damaged and even concretely unable. In that sense, the text intends to show 'the desire of affections control and the organization to humanity domestication' as the major subject, based on Theodor Adorno’s and Max Horkheimer’s criticism about the "cultural industry" of the late capitalism. In spite of it, because the 'control', the ethics (human condition) is attacked and misunderstood. Due to the central problem, it will show the purpose of ethics neutralization into human relationships. Of course such a coercive employment turns off the ‘time’, therefore it also wants to avoid changes like 'social pacts' that means presumption behavior to keep going with certain politicy. This deletion, for ontological emphasis, is the disposition of difference control, that doesn’t give a way to manifest itself concretely. ‘Time’ testifies the ethics at the same time that is where the ethics takes place. This argumentation aims to criticize the rationality that shut up the difference, neutralizes time and ethics and also wants to tame life, entangling it in formalisms.